STRATEGI PENGEMBANGAN BALI ZOO PARK SEBAGAI DAYA TARIK WISATA DI KABUPATEN GIANYAR BALI - Sarwa Edy, Raden Agus; Widyastuti, Ni Kadek (Jurnal Manajemen Pelayanan Hotel, 2021)
Development in the tourism sector remains the leading sector in economic development in Bali. The development of tourism has a considerable influence on economic growth in Indonesia in general and Bali in particular. For this reason, the Balinese government through the Tourism Office and other relevant agencies continues to strive to improve and organize existing tourist attractions and develop these tourist attractions so that more and more tourist come. One of them is Bali Zoo Park which is located in Gianyar Regency, Bali. With the development of tourist attractions, especially those that offer animal attractions that can attract tourist, Bali Zoo Park continues to improve because it sees many competitors who also offer the same attractions. Bali Zoo Park is a wildlife sanctuary visited by many tourists, both domestic and foreign tourist. Many animals are protected in Bali Zoo Park and even animals that are almost extinct such as the Bali Startling, Peacock, Cassowary, and Cockatoo besides that there are many other animal collections such as deer, kangaroos, reptiles, primates, tigers and many other species. With so many competitors who also offer the same attractions, Bali Zoo Park has developed a development strategy so that it can continue to exist so that more tourists visit. The types of data use in this research are quantitative and qualitative data, and the data collection techniques used are through observation, interviews, questionnaires and documentation. The strategy for developing Bali Zoo Park as a tourist attraction is carried out using a SWOT analysis by considering internal and external factors, namely Strength, Weaknesses, Opportunities, and Threats. Keywords: Development strategy, Tourism attractiveness Business